The handbook of linguistics - Aronoff, Mark; Rees-Miller, Janie (Hoboken : Wiley-Blackwell, 2017)
'The Handbook of Linguistics is a general introductory volume designed to address this gap in knowledge about language'--
Starting Points. Origins of Language / Andrew Carstairs-McCarthy -- Languages of the World / Bernard Comrie -- Typology and Universals / William Croft -- Field Linguistics: Gathering Language Data from Native Speakers / Pamela Munro -- Writing Systems / Peter T Daniels -- Theoretical Bases. The History of Linguistics: Approaches to Linguistics / Lyle Campbell -- Generative Grammar: Rule Systems for Describing Sentence Structure / Thomas Wasow -- Functional Linguistics: Communicative Functions and Language Structure / Robert D Van Valin -- Core Fields. Linguistic Phonetics: The Sounds of Languages / John Laver -- Phonology: Sound Structure / Abigail C Cohn -- Morphology / Andrew Spencer -- The Lexicon / D A Cruse -- Syntax / Mark C Baker -- Formal Semantics / Shalom Lappin -- Historical Linguistics: Language Change Over Time / Brian D Joseph -- Languages and the Mind. Neurolinguistics / David Caplan -- Psycholinguistics / Kiel Christianson -- Sign Languages / Wendy Sandler, Diane Lillo-Martin -- First Language Acquisition / Brian MacWhinney -- Languages in Use. Pragmatics: Language and Communication / Ruth Kempson -- Discourse Analysis / Agnes Weiyun He -- Linguistics and Literature / Nigel Fabb -- Linguistic Anthropology and Ethnolinguistics / Steven P Black, Elizabeth A Falconi -- Sociolinguistic Theory: Systematic Study of the Social Uses of Language / J K Chambers -- Language Variation: Sociolinguistic Variationist Analysis / Kirk Hazen -- Multilingualism / Suzanne Romaine -- Second Language Acquisition: One Person with Two Languages / Vivian Cook -- Applications of Linguistics. Second Language Pedagogy: Where Theory Meets Practice / Janie Rees-Miller -- Educational Linguistics / James Paul Gee -- Linguistics and Reading / Rebecca Treiman -- Language and Law / Roger W Shuy -- Translation / Christoph Gutknecht -- Language Planning and Policy / Kathryn D Stemper, Kendall A King.
Includes index.
Print version record.
Keywords: Linguistics -- Handbooks, manuals, etc; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; Linguistics; LANGUAGE ARTS & DISCIPLINES / Linguistics / Historical & Comparative; Handbooks and manuals; Electronic books